Analisis Pengaruh Pembiayaan Baitul Maal Wat Tamwil Terhadap Perkembangan Usaha Nasabah (Studi Kasus Di BMT Pradesa Mitra Mandiri Kabupaten Langkat) - Y Yuliani; Zainul Fuad; N Nurasiah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2019)
Some of the problems faced by small businesses most importantly are capital problems for business development. Because of the difficulty of accessing capital, business development is hampered which results in businesses run by business actors not running smoothly, BMT Pradesa Mitra Mandiri provides solutions by providing financing to prospective customers who lack capital to run a business. This study aims to analyze the effect of financing provided by BMT Pradesa Mitra Mandiri on the development of customer business before and after getting financing, business development indicators in this study are, how the venture capital, sales turnover and business profits after and before getting financing. This type of research used in this study is a descriptive method with a quantitative approach. The sample in this study used a non-probability method with a purposive sampling technique. The sample used is the customer members who get financing from BMT Pradesa Mitra Mandiri with a sample of 40 respondents. Data collection technique using questionnaires, interviews and observations. Data analysis techniques used in this study were descriptive analysis techniques through validity, reliability, and Paired T-test with SPSS 18. The results showed that the funding provided by BMT Pardesa Mitra Mandiri greatly influenced the development of customer business in the area of Langkat District, as evidenced by the results of the study showing that venture capital, sales turnover and business profits had increased between before and after getting financing from BMT Pradesa Mitra Mandiri.